Biological bases of optimization of training loads of athletes - Minjunke Shan,; Kozhedub M.S. ,; Vrublevskiy E.P. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to study the main approaches of coaches in Belarus and China to taking into account the biorhythmic characteristics of the body of athletes when planning their training process and to determine the dynamics of the manifestation of speed-strength abilities during OMC in female athletes specializing in various sports. Methods and structure of the study. A questionnaire was developed and a survey was conducted of coaches (n=16) involved in training female athletes in the Republic of Belarus and specialists (n=12) who train female hockey players in China. Also, to determine well-being, changes in mental state, performance, tolerance of training and competitive loads in various phases of the body’s biorhythmics, a survey and testing of 18 qualified Belarusian female runners at various distances and 23 Chinese female hockey athletes was conducted. Results and conclusions. Analyzing the data from a survey of coaches, it can be stated that most specialists, when planning the training process, do not take into account the phase nature of the ovarian-menstrual cycle of female athletes, which negatively affects the tolerance of the proposed loads, the functional state and well-being of girls. The results of the survey and the results of testing of female athletes indicate the presence of significant phase changes in the indicators of motor abilities of female runners and hockey players in each of the phases of the ovarian-menstrual cycle.